NAVIGATING INTERCULTURAL SPACES: A COMPARATIVE ANALYSIS OF COMMUNICATION BARRIERS, DIGITAL MEDIA UTILIZATION, AND ADAPTATION EXPERIENCES AMONG IISMA AWARDEES IN SOUTH KOREA AND MALAYSIA - Melly Ridaryanthi; Vinka Patricia; Yuni Tresnawati; Eka Perwitasari Fauzi; Abdul Latiff Ahmad (MediaKom : Jurnal Ilmiah Komunikasi, 2026)
This study examines the intercultural adaptation experiences of Indonesian undergraduate students participating in the Indonesian International Student Mobility Awards (IISMA) program, comparing awardees placed in South Korea (Hanyang University) and Malaysia (Universiti Kebangsaan Malaysia). Adopting a constructivist qualitative paradigm rooted in communication scholarship, the research investigates the interplay between cultural distance, verbal and non-verbal barriers, and contemporary digital mediation through theories of Anxiety/Uncertainty Management (AUM) and Integrative Cross-Cultural Adaptation. Data collected from in-depth interviews and institutional reports reveal that distinct cultural landscapes shape unique communicative hurdles. Awardees in South Korea faced a significant linguistic divide, rigid non-verbal hierarchies, and the pressures of an accelerated urban lifestyle (ppali-ppali). Conversely, awardees in Malaysia dealt with the subtle complexities of a multicultural society and semantic shifts within a false linguistic proximity. Across both cohorts, digital media platforms functioned as crucial adaptive mediators, providing real-time translation, logistical navigation, and psychological coping mechanisms through co-ethnic social networks. Ultimately, the findings demonstrate that overcoming these communication barriers facilitates personal and intercultural growth, illustrating the classic stress-adaptation-growth dynamic and highlighting the value of context-specific institutional preparation for international student mobility.